2021
DOI: 10.3390/met11020305
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Welding Parameters and Filler Material on the Mechanical Properties of HSLA Steel S960MC Welded Joints

Abstract: This article provides an overview of the influence of welding parameters and filler material on changes in the heat-affected zone (HAZ) of thermo-mechanically controlled processed (TMCP) steel welded joints. The research focused on evaluating the effect of heat input and cooling rate on the width of the soft zone, which significantly affects the mechanical properties of welded joints. The negative effect of the soft zone is more pronounced as the thickness of the material decreases. Therefore, the object of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…Because of its excellent mechanical properties, DOMEX 700 is primarily used to fabricate cranes for the heavy construction industry. Mician et al [15] reported that the combination of qualities found in TMCP steels, including superior strength, enhanced toughness, and weldability, makes them a potential candidate for various applications, such as heavy vehicles crane booms, earthmovers, etc. Similarly, the S960MC steel grade meets these requirements.…”
Section: Historical Development Of Ahssmentioning
confidence: 99%
See 3 more Smart Citations
“…Because of its excellent mechanical properties, DOMEX 700 is primarily used to fabricate cranes for the heavy construction industry. Mician et al [15] reported that the combination of qualities found in TMCP steels, including superior strength, enhanced toughness, and weldability, makes them a potential candidate for various applications, such as heavy vehicles crane booms, earthmovers, etc. Similarly, the S960MC steel grade meets these requirements.…”
Section: Historical Development Of Ahssmentioning
confidence: 99%
“…The fine-grained microstructure generated by the TMCP method also ensures that S960MC steels have high strength and good formability. The Nb, Ti, and V elements play a predominant role because they generate dispersive precipitates which provide precipitation strengthening [15,16,56,57]. The precipitate strengthening supplied by Nb strengthens steel using carbonitrides particles.…”
Section: Weldability Challenges Due To Alloying Elementsmentioning
confidence: 99%
See 2 more Smart Citations
“…The engineering steels have changed from ordinary carbon steels (e.g., Q345 [8]) to high-strength steels (e.g., Q690 [9] or even Q960 [10]). For the welding of high strength steel, a lot of current research has focused on the process windows of different welding methods [11][12][13][14][15], the influence of alloying elements on weldability [16][17][18], the matching and upgrading of welding wire [19][20][21], and the failure of welded joints [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%